Tumour-reactive B cells and antibody responses after allogeneic haematopoietic cell transplantation. (September 2020) - de Jong, G.; Gillissen, M.A.; Spits, H.; Hazenberg, M.D.
Abstract : For many high-risk haematologic malignancies, such as acute myeloid leukaemia, the success of therapy relies mainly on invoking a curative antitumour immune response. This can be achieved by inducing a graft-versus-leukaemia response following allogeneic haematopoietic cell transplantation. While the contribution of T cells and natural killer cells to graft-versus-leukaemia responses is established, the contribution of B cells and antibodies is relatively unexplored. This article reviews what is known about the contribution of B cells and tumour-specific antibody responses to a successful graft-versus-leukaemia response leading to eradication of the tumour. Highlights: B cells play a role in graft-versus-leukaemia (GvL) responses after allogeneic haematopoietic cell transplantation. Targets of GvL B-cell responses are not unique to individual patients. Tumour antigens are shared between haematologic and non-haematologic tumours. GvL antibodies may be employed for the development of novel immunotherapies.